Associations of non-invasive indices of liver steatosis and fibrosis with progressive kidney impairment in adults with type 2 diabetes - Moh, Mei Chung (2024)
Aims: Longitudinal data linking non-alcoholic fatty liver disease to kidney dysfunction in type 2 diabetes (T2D) are limited. This study evaluated the associations of non-invasive indices of liver steatosis and liver fibrosis with kidney impairment, and the mediatory role of the pro-angiogenic factor leucine-rich α-2 glycoprotein 1 (LRG1). Methods: T2D adults (n = 2057) were followed for a mean period of 6.1 ± 1.6 years. Baseline liver steatosis [(hepatic steatosis index (HSI) and Zhejiang University index (ZJU)] and liver fibrosis [aspartate transaminase/alanine transaminase ratio (AAR) and BARD] indices derived from composite scoring systems were calculated. Plasma LRG1 levels were quantified using immunoassay. The study outcomes were progressive kidney function decline defined as estimated glomerular filtration rate (eGFR) decline of ≥ 40% and albuminuria progression defined as an increase in albuminuria category. Results: Cross-sectionally, liver steatosis and liver fibrosis indices were associated with increased albuminuria (urinary albumin/creatinine ratio ≥ 30 µg/mg) and reduced renal function (eGFR < 60 mL/min/1.73 m2) after covariate adjustment, respectively. Approximately 32% of the participants experienced progressive kidney function decline, while 38% had albuminuria worsening over time. Longitudinal analysis revealed that baseline AAR (hazard ratio: 1.56; 95% CI 1.15–2.11) and BARD (hazard ratio: 1.16, 95% CI 1.04–1.28) predicted progressive kidney function decline, partly mediated by LRG1. In contrast, liver steatosis (HSI and ZJU) but not liver fibrosis (AAR and BARD) indices were independently associated with albuminuria progression. Conclusions: Increased liver steatosis scores were associated with albuminuria deterioration. Conversely, liver fibrosis indices may be associated with progressive kidney function decline, potentially driven by increased inflammation and angiogenesis.